Acute Kidney Injury in a Single Pediatric Intensive Care Unit in Poland: A Retrospective Study - Monika Miklaszewska; Przemysław Korohoda; Alina Sobczak; Anna Horbaczewska; Agata Filipiak; Katarzyna Zachwieja; Krzysztof Kobylarz; Marcin Tkaczyk; Dorota Drożdż; Jacek A. Pietrzyk (Karger Publishers, 2014)
Background/Aims: The recent improvements of management of patients in pediatric intensive care units (PICU) are associated with improved outcome. However, this decrease in mortality is associated with an increased number of children with acute kidney injury (AKI), especially in patients with multiorgan failure. Methods: The report presents a retrospective analysis of 25 cases of AKI (assessed based on the pRIFLE criteria) in PICU within 7 years. Results: AKI was diagnosed in 1.24% of all hospitalized children. AKI percentage duration (as compared to the total hospitalization time) in the children who died vs. the survivors was 79.55% vs. 46.19%, respectively (pvs. 49% in non-oliguric children. Averaged urine output values in the first week of hospitalization in the deceased vs. survivors were 1.49 vs. 2.57 ml/kg/h, respectively (pConclusions: Oliguria should not be considered as a sensitive parameter for AKI diagnosing in children below one year of age. A decreased mean urine output in the first week of PICU hospitalization (less than 1.4 ml/kg/h) should be considered as a poor prognostic factor. In many cases AKI was diagnosed too infrequently and too late.